A prospective study of clinical and histopathological correlation of specimens of hysterectomies - Rastogi, Radha; Tailor, Bharat; Patidar, Vandana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Uterus, a vital reproductive organ is subjected to many benign and malignant diseases. Although many medical and conservative surgical treatment options are available, hysterectomy still remains the most commonly performed major gynaecological operative procedure worldwide. Mostly it is the definitive treatment for many of its indications including abnormal uterine bleeding, like in case of fibroids, adenomyosis, utero-vaginal prolapse, endometriosis and pelvic inflammatory disease. Aims and objectives were to know the indications for hysterectomy and its various complications and to analyse correlation between the clinical indication with their histopathological findings. Methods: This hospital based study was conducted at RNT Medical College, Udaipur. A total of 200 case were included undergoing hysterectomy (any route) for gynecological disease. Surgical specimens were sent for histopathology and reports were analysed and compared with the indications of surgery. Results: In this study preoperative indication of hysterectomy was leiomyoma (34.50%) followed by utero vaginal prolapse (39.0%) and adenomyosis (12.5%) etc. Common finding of HPR report of specimens of uterus and adnexa are as follows: endometrium- proliferative phase (44.50%), myometrium- leiomyoma (33%), cervix- mild squamous hyperplasia (45%), ovaries- physiological ovarian cyst (25.50%). Pre-operative diagnosis of all cases of study were confirmed on histopathology. There was no major intraoperative complication in study group like bladder, rectum, ureter, visceral organ injuries etc. There was no life-threatening postoperative complication and all patients were discharged in good general condition. Conclusions: In most cases diagnosis by HPR was similar with our preoperative diagnosis but in few cases HPR diagnosis may differ from preoperative diagnosis. Major complications were negligible, hence now-a-days hysterectomy is considered quite a safe procedure.